Effect of hyperelastic pre-stretching on thickness distribution of pressure thermoformed products. (February 2023) - Patil, Jeet; Gaikhe, Yogesh; Vasavada, Jitesh; Mishra, Sushil
Pressure thermoforming is one of the most used processes, but the thickness gradient in the formed parts limits its application. To control the product thickness distribution, pressure forming is assisted by a punch. However, due to punch contact with the sheet, the process is susceptible to surface defect, which is detrimental to the optical properties of the product. To produce optical parts with zero surface defects and controlled thickness distribution, a novel approach as a means for dimensional control by sheet pre-stretching is proposed and validated numerically. It was found that pre-stretching has a significant effect on the deformation behavior of the product.